2009
DOI: 10.1111/j.1600-0668.2009.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and predictor determination of indoor aldehyde levels in Paris newborn babies’ homes

Abstract: This analysis contributed to document indoor aldehyde levels in Parisian homes and to identify factors determining these levels. In the major part of newborn babies' homes, indoor formaldehyde levels were above the guideline value of 10 microg/m(3) proposed by the French Agency for Environmental and Occupational Health Safety for long-term exposure. Given this result, it is essential to study the health impact of exposure to aldehydes especially formaldehyde on the incidence of respiratory and allergic symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 30 publications
2
32
0
1
Order By: Relevance
“…A study of exposure at age 1 month and subsequent diagnosed rhinitis at 18 months found that the introduction of particle-board furniture less than 12 months old in the bedroom was associated with an increased risk of non-allergic rhinitis (OR 1.87, 95% CI 1.21-2.90) [10]. Aldehydes, particularly formaldehyde, were found to be the major pollutant in particle-board less than 1 year old after manufacture reported by the same group, and were associated with an increased risk of rhinitis [29]. Until now, many studies emphasized the association between prenatal exposure to tobacco smoke and children's respiratory health later in life [7,30,31], and gave less attention to new furniture/decoration.…”
Section: Resultsmentioning
confidence: 83%
“…A study of exposure at age 1 month and subsequent diagnosed rhinitis at 18 months found that the introduction of particle-board furniture less than 12 months old in the bedroom was associated with an increased risk of non-allergic rhinitis (OR 1.87, 95% CI 1.21-2.90) [10]. Aldehydes, particularly formaldehyde, were found to be the major pollutant in particle-board less than 1 year old after manufacture reported by the same group, and were associated with an increased risk of rhinitis [29]. Until now, many studies emphasized the association between prenatal exposure to tobacco smoke and children's respiratory health later in life [7,30,31], and gave less attention to new furniture/decoration.…”
Section: Resultsmentioning
confidence: 83%
“…Items investigated in the questionnaire were collected in the literature and in similar studies carried out previously (Dassonville et al, 2009;Roda et al, 2011). The questionnaire included general information about the building (period of construction and renovation, surface, number of rooms), specific information about the rooms where sampling was carried out (child's bedroom and living-room) and the kitchen, often directly linked to the living-room (floor, wall and ceiling materials, presence of pressed-wood furniture, heating and ventilation systems), daily living habits in general and specifically during the sampling period (heating, aeration, cooking, type and frequency of cleaning, number of occupants and pets, specific activities or use of specific products).…”
Section: Questionnairementioning
confidence: 99%
“…It is mainly produced by off-gassing from wood-based products assembled using urea-formaldehyde resins but can also be generated by cigarette smoking, painting, or the use of varnishes and floor finishes [9,10]. VOCs are chemical compounds including aromatic hydrocarbons, aldehydes, aliphatic halogenated hydrocarbons and terpenes.…”
Section: Indoor Air Pollutants and Relative Sourcesmentioning
confidence: 99%